Photosynthetic hydrogen production: Novel protocols, promising engineering approaches and application of semi‐synthetic hydrogenases. Issue 2 (2nd May 2021) - Kosourov, Sergey; Böhm, Maximilian; Senger, Moritz; Berggren, Gustav; Stensjö, Karin; Mamedov, Fikret; Lindblad, Peter; Allahverdiyeva, Yagut
Abstract: Photosynthetic production of molecular hydrogen (H2 ) by cyanobacteria and green algae is a potential source of renewable energy. These organisms are capable of water biophotolysis by taking advantage of photosynthetic apparatus that links water oxidation at Photosystem II and reduction of protons to H2 downstream of Photosystem I. Although the process has a theoretical potential to displace fossil fuels, photosynthetic H2 production in its current state is not yet efficient enough for industrial applications due to a number of physiological, biochemical, and engineering barriers. This article presents a short overview of the metabolic pathways and enzymes involved in H2 photoproduction in cyanobacteria and green algae and our present understanding of the mechanisms of this process. We also summarize recent advances in engineering photosynthetic cell factories capable of overcoming the major barriers to efficient and sustainable H2 production.